2022
DOI: 10.1007/s10815-021-02379-8
|View full text |Cite
|
Sign up to set email alerts
|

Importance of IGF-I levels in IVF: potential relevance for growth hormone (GH) supplementation

Abstract: Purpose Growth hormone (GH) supplementation in association with in vitro fertilization (IVF) is worldwide again increasing, even though study outcomes have been discrepant. Since GH acts via insulin-like growth factor-1 (IGF-1), its utilization in IVF would only seem to make sense with low IGF-1. We, therefore, determined whether IGF-I levels affect IVF outcomes. Methods Retrospectively, 302 consecutive first fresh, non-donor IVF cycles were studied, exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The median age was 35.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Group-I, 29.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) in Group-II, and 33.0 in Group-III, and the difference between the groups was statistically significant (p<0.001). The mean BMI was 23.55 in Group-I, 23.1 in Group-II, and 24.0 in Group-III (p=0.751).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The median age was 35.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Group-I, 29.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) in Group-II, and 33.0 in Group-III, and the difference between the groups was statistically significant (p<0.001). The mean BMI was 23.55 in Group-I, 23.1 in Group-II, and 24.0 in Group-III (p=0.751).…”
Section: Resultsmentioning
confidence: 96%
“…A recent study about GH and infertility, investigated the pregnancy results depending on the serum IGF-1 levels (Groups; <25 th percentile, 25 th -75 th percentile, >75 th percentile) 37 . The cycle cancellation rates were highest in the IGF-1 <25 th percentile group.…”
Section: Discussionmentioning
confidence: 99%
“… 242 In addition, serum IGF1 levels decline with age, which correlates with the well‐known decrease in fertility due to aging. 243 These findings underscore the close interaction between FSH and IGFs in regulating human follicle development.…”
Section: Igf1r and Fshr Crosstalk And Female Infertilitymentioning
confidence: 85%
“…Therefore, to enhance oocyte yield, it seems more appropriate to initiate GH co-treatment before commencing ovarian stimulation, which is consistent with the regularity of follicle growth and maturation. Gleicher and colleagues endorsed this hypothesis and suggested that the administration of GH should at least 6 weeks prior to COH 64 . In this NMA, we have found that compared to the control group, using GH at a dosage > 8 IU/day for at least 2 weeks before oocyte retrieval could improve the number of obtained oocytes in POR patients but did not show significant advantages compared to the medium dose, follicular phase protocol (protocol D).…”
Section: Endometrial Thickness On Hcg Daymentioning
confidence: 99%